Lipidation status of single membrane-associated ATG8 proteins. Issue 10 (October 2021) - Viret, Christophe; Faure, Mathias
Abstract : ATG8 are core autophagy proteins, the lipidated forms of which decorate double-membraned autophagosomes, as well as single-membraned organelles such as endolysosomes. Recent studies from the Florey and Münz laboratories delineate the status of single membrane-associated ATG8 proteins by indicating that their membrane anchoring can involve phosphatidylserine conjugation and their stabilization depends on ATG4 protease inhibition.